Individualized Analysis and Treatment of Difficult Weaning From Ventilation Following Open Cardiac Surgery in Young Children With Congenital Heart Disease - Wu, Xiaoming; Chen, Jinlan; Iroegbu, Chukwuemeka Daniel; Liu, Jian; Wu, Ming; Xie, Xia; Xiang, Kun; Wu, Xun; Chen, Wangping; Huang, Peng; Zhou, Wenwu; Fan, Chengming; et al. (Frontiers in Cardiovascular Medicine, 2022)
Aims The study explores the leading causes of postoperative extubation difficulties in pediatric patients (neonates and toddlers) with congenital heart diseases and establishes individualized treatment for different reasons. Method We retrospectively analyzed medical records of 4,971 pediatric patients with congenital heart defects treated in three tertiary Congenital Heart Disease Centres in China from January 2005 to December 2020, from whom we selected those with difficulty extubation but successful weaning during the postoperative period. Next, we performed an analysis of risk factors and reported the combined experience of individualized treatment for successful extubation. Results Seventy-five pediatric patients were identified in our database, among whom 23 had airway stenosis, 17 had diaphragmatic dysfunction, and 35 had pulmonary infection. The patients were all successfully weaned from the ventilator after an individualized treatment plan. In addition, the intubation time in the airway stenosis group was 17.7 ± 9.0, 33.6 ± 13.9 days in the diaphragmatic dysfunction group, and 11.9 ± 3.8 days in the pulmonary infection group. Conclusion Given the primary reasons for difficult weaning following open-heart surgery in pediatric patients with congenital heart diseases, an individualized treatment scheme can achieve the ideal therapeutic effect where patients can be weaned faster with a shorter intubation period.